Fighting crosswinds in cycling: A matter of aerodynamics - Beaumont, Fabien; Bogard, Fabien; Murer, Sébastien; Polidori, Guillaume (Journal of Science and Medicine in Sport, 2023)
Objectives The main goal of this study was to compare the aerodynamic optimization level in echelon-formation strategy for riders fighting against a crosswind from the best (echelon or diagonal paceline) to the worst riders' configuration (guttered riders). Design The case reported herein concerned a group of 5 cyclists riding at 30 km/h with a 30 km/h crosswind oriented at 40° to the direction of travel. The effects of the wind, expressed in terms of aerodynamic resistance or pressure, were determined for each cyclist in the different configurations. Methods The 3D numerical simulations were performed using a calculation code based on the finite volume method and the Reynolds-averaged Navier–Stokes turbulence model k–kl–ω. Results The results showed that the lateral force savings, averaged over the whole five-riders group, ranged from 50% in the echelon-optimized configuration to 11% in the guttered straight-line one, compared to a solo rider in the same velocity and windy conditions. Individually, the rider with the best aerodynamic shelter is the 4th rider in the “4 rider echelon + 1 guttered rider” formation (− 53.6% in drag force and − 69.8% in lateral force), while the rider with the worst aerodynamic situation is the leader of the straight paceline (− 0.1% in drag force and − 0.2% in lateral force). Conclusions The analysis showed how the spatial management of riders significantly influences drag and lateral forces and supported the idea that avoiding being guttered is the best way to save energy in windy races.
Keywords: Aerodynamics; CFD; Crosswind; Cycling; Drafting; Turbulence